Current Standards and Recent Advances in Biomarkers of Major Endocrine Tumors - Luo, Yanhong; Zhu, Hua; Tan, Tao; He, Jianfeng (Frontiers in Pharmacology, 2018)
The complexity of endocrine tumor diagnosis stems from its variable symptoms and presentation that may mimic many other disease states, or display asymptomatic properties for a prolonged amount of time. Early and accurate disease identification is needed for patient prognosis. The key to this may be in using validated biomarkers with increased sensitivity and specificity. Several biomarkers are consistent across various endocrine tumor types, possibly indicating a deeper pathophysiological mechanism behind endocrine cancer genesis and development. For example, carbohydrate antigen is measured in both pancreatic adenocarcinoma as well as ovarian cancer for diagnosis, surveillance, and risk stratification. The discovery of measuring miRNAs that are highly expressed in malignant tumors is also a novel strategy across multiple endocrine tumor types, and is propelling the future advancement of biomarker development. This review introduce some currently utilized biomarkers in some of the common endocrine tumors, including thyroid, adrenal, pituitary, pancreatic, and gonadal carcinoma, as well as future research directions.